EXPERT SYSTEM FOR DIAGNOSING HEART DISEASE USING WEB-BASED ANALYTIC HIERARCHY PROCESS AND CERTAINTY FACTOR METHODS - Hakim, Lukman; Wicaksono, Freddy; Bhakti, M.Herdian (INTI TALAFA, 2025)
Health is the most valuable thing for humans, one example is that humans often forget about their heart health. The heart is one of the organs of the body that is very vital and has a very important role for humans. Basically, heart disease is often called a “silent killer”, based on World Health Organization (WHO) data that heart disease is the number one cause of death in the world. Therefore, a system is needed to help prevent heart disease and provide the right diagnosis and solution. This study aims to design a web-based expert system for diagnosing symptoms of heart disease in humans using the Analytical Hierarchy Process (AHP) and Certainty Factor (CF) methods. The Analytical Hierarchy Process (AHP) method determines the weight of the expert, while the Certainty Factor method calculates the diagnosis of user disease symptoms. The final results of the system show that the system is able to diagnose heart disease through the symptoms selected by the user. The system can also provide descriptions and appropriate handling solutions for diseases experienced by users.       Kata kunci: Sistem Pakar, Penyakit Jantung, Analytical Hierarchy Process, Certainty Factor